Self-government investments and their funding in a year and multi-year perspective (Economic and Political Thought, 2014)
Commune investment constitutes one of the most important factors in localdevelopment. It is an important condition for enhancing the implementationof municipal engineering and social services and the growth of the municipalassets, the improvement of the level of services provided in terms of qualityand quantity, the creation of conditions for setting up new businesses and thesettlement of new inhabitants. There is a common feature of self-governments’investment – a necessity to involve a certain capital, usually for a long term,which is connected with uncertainty and a risk to achieving the plannedbenefits. Therefore, it is very important to select appropriate sources offunding and skilful investment project management. There are some typicalfeatures and conditions of each source of funding. The self-governments’task is to select them skilfully so that the effects of tasks implementationare adequate to local communities’ expectations. One of the conditions forachieving the planned aims is an in-depth knowledge of both the mechanismsof raising and possibilities of using their own and additional income as well asrepayable sources of funding. The eventual choice of funding sources resultsfrom analyses results and the development of alternative funding scenarios.One cannot speak about a universal investment funding structure good forevery unit and every project. It depends on various factors connected withthe specificity of a given commune, county or voivodeship and the featuresof the particular investment.